Estimated base temperature for leaf appearance and phyllochron of mate herb during the seedling phase - Poleto, Gian Carlos; Paula, Gizelli Moiano de; Caron, Braulio Otomar; Elli, Elvis Felipe (Revista Ecologia e Nutrição Florestal - ENFLO, 2017)
Mate herb (Ilex paraguariensis St. Hil.) is a native of Brazil, Argentina and Paraguay. The cultivation of this species is one of the oldest and characteristic agroforestry systems in southern Brazil, assuming significant environmental and socioeconomic importance. The aim of this study was to estimate the base temperature for leaf appearance and phyllochron in the mate herb phase change An experiment was conducted in a nursery at the Federal University of Santa Maria campus Frederico Westphalen. It was used a completely randomized design was used, with three different times of transplanting with twenty repetitions each. The base temperature (Tb) was estimated using the methodology of the minimum mean square error (MSE) and the phyllochron was obtained by the inverse of the slope of the linear regression between the number of leaves, and the accumulated thermal. Tb was 8.5 °C and phyllochron estimated ranged from 393.27 °C day leaf-1 to 401.01 °C day leaf-1, in mate herb seedlings.